2016
DOI: 10.1111/ibi.12374
|View full text |Cite
|
Sign up to set email alerts
|

Interactive vocal communication at the nest by parent Great TitsParus major

Abstract: Although most bird species show monogamous pair bonds and bi‐parental care, little is known of how mated birds coordinate their activities. Whether or not partners communicate with each other to adjust their behaviour remains an open question. During incubation and the first days after hatching, one parent – generally the female – stays in the nest for extended periods, and might depend on acoustic communication to exchange information with its mate outside. The Great Tit Parus major is an interesting study sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…In follow up studies, Boucaud, Vignal, and collaborators further demonstrated that females may signal their immediate needs to their partner by vocalizing from inside the nest when the male arrives in the vicinity (Boucaud et al, 2016c(Boucaud et al, , 2017. In wild zebra finches, female calling rate and her calls' acoustic structure on her mate arrival predicted whether or not the male relieved the female for incubation (Boucaud et al, 2017).…”
Section: Vocal Negotiation Between Breeding Partnersmentioning
confidence: 97%
See 1 more Smart Citation
“…In follow up studies, Boucaud, Vignal, and collaborators further demonstrated that females may signal their immediate needs to their partner by vocalizing from inside the nest when the male arrives in the vicinity (Boucaud et al, 2016c(Boucaud et al, , 2017. In wild zebra finches, female calling rate and her calls' acoustic structure on her mate arrival predicted whether or not the male relieved the female for incubation (Boucaud et al, 2017).…”
Section: Vocal Negotiation Between Breeding Partnersmentioning
confidence: 97%
“…great tits (Parus major), with female-only incubation, female's vocalisations, and the pair's vocal interactions differed depending on whether or not the male entered the nest to feed the female (Gorissen and Eens, 2005;Boucaud et al, 2016c). Moreover, when great tit females were experimentally supplemented with food, they altered their vocalisations, uttered before and after the male entered the nest (Boucaud et al, 2016b).…”
Section: Vocal Negotiation Between Breeding Partnersmentioning
confidence: 99%
“…During this period, the male and female have brief vocal exchanges where the male sings from a perch and the female answers predominately with calls ( Gorissen and Eens, 2004 ; Boucaud et al, 2016b , c ). These vocal exchanges are longer and more rapid when the male feeds the female ( Boucaud et al, 2016c ), and experimentally manipulating food availability shows that females use calling as an honest indicator of their hunger levels ( Boucaud et al, 2016b ). These lines of work emphasize that much behaviorally relevant information can be communicated in these coordinated nesting exchanges.…”
Section: Behavioral Coordination and Biparental Care In Birdsmentioning
confidence: 99%
“…Inspection of tit nests may be risky for flycatchers, as they may even be killed by nest owners Samplonius and Both 2019). Although flycatchers could probably reduce the mortality risk by determining tit nest box occupation and stage from outside the box, based on the intra-pair vocal activity of tits (Baucaud et al 2016), assessing tit clutch size would require entering the nest. The access to tit nests will be reduced and riskier during the incubation stage, when female tits spend more time in the nest than during egg laying (Slagsvold and Wiebe 2017).…”
Section: Prospecting For Interspecific Information In Flycatchers-thementioning
confidence: 99%